When the body organizes itself: Organic pluralism and political community in Luigi Sturzo and Ramiro de Maeztu - Clemente Yanes, Enrique (Historia y Política, 2025)
Studies on organicism in interwar Europe have largely focused on identifying convergences and divergences among various models–fascism, social Catholicism–while consistently emphasizing its anti-liberal character and the authoritarian matrix that underpins it. However, there is another history that does not contradict this narrative, but rather complements and enriches it. Organicism is an ambiguous term which, in the context of interwar Europe, did not assume a univocal meaning. It lent itself to interpretations far removed from the authoritarianism that brought an end to the long liberal summer inaugurated after the Franco-Prussian War. Specifically, this pluralist variant called for a dismantling of national sovereignty —the foundational myth of liberal revolutions—based on the reality of intermediate social groups: local communities, trade unions, associations, cooperatives…To follow the metaphor, the various articulations of the body were to possess enough autonomy not to become atrophied by the central nervous system— the State. This article analyzes the pluralist proposals of Luigi Sturzo and Ramiro de Maeztu within a shared context: the experience of the Great War, their time in London and involvement in contemporary intellectual circles, and the Catholic ethos that shaped both thinkers’ political visions